Cancer situación in Peru - Vallejos-Sologuren, Carlos S. (2020)
Cancer is one of the public health problems in many countries or regions of the world. The incidence, mortality, and prevalence of cancer allow us to quantifying the magnitude of this pathology and guide public policies concerning prevention and health services. The high economic and social cost that the care of these patients represents means that the prevalence, form of evolution, and prognosis differ from one country to another. In Peru, cancer represents the leading cause of death. By 2018, according to Globocan, more than 66,000 new cases were diagnosed and more than 33,000 deaths from cancer were registered. The three most common pathologies in women were breast cancer (19%), cervical (11%) and stomach cancer (7%), and in men prostate cancer (25%), stomach (10%) and cancer colorectal (7%); and the main causes of death were stomach (13.9%), lung (8.6%) and prostate cancer (8.2%). The incidence rate was 192.6 and the mortality rate 92.9 per 100,000 people, respectively; depending on the location of the tumor, the incidence rate for prostate cancer was 47.8, breast 40.0, cervical 23.2 and stomach 16.1 per 100,000 people, respectively, and the mortality rate for prostate cancer was 15.6, stomach 12.8, breast 10.3 and cervical 10.2 per 100,000, respectively. The estimated prevalence at one year was 42,849 cases, at three years 104,007 and 5-years 150,132 cases; the most prevalent pathologies in men were prostate, colorectal and NHL cancer, and in women were breast, cervical and thyroid cancer. Mortality and incidence rates, which allow quantifying the lethality of the disease in our environment, remain high in neoplasms such as the liver, pancreas, stomach and lung cancer. The incidence and mortality rates due to cancer continue to increase in our population in relation to the 2012 report; these increases may be a consequence of changes in the population's age structure, adoption of sedentary lifestyles, unhealthy diets and among other factors.